The complete mitochondrial genome of the Greater Mouse-Eared bat, Myotis myotis (Chiroptera: Vespertilionidae). (4th May 2017) - Jebb, David; Foley, Nicole M.; Puechmaille, Sébastien J.; Teeling, Emma C.
Abstract: In this study, we report the complete mitochondrial genome of the Greater Mouse-Eared Bat, Myotis myotis. The mitogenome is 17 213 bp with base composition A (34.2%), G (13%), C (22.4%), and T (30.5%). The genome shows conserved synteny with other mammalian mitogenomes, containing 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and 1 control region (D-Loop). The majority of the genes are encoded on the H-Strand, except for ND6 and eight tRNAs. All protein-coding genes start with the ATG start codon, except for ND2, ND3, and ND5 which begin with ATT or ATA. Seven protein-coding genes terminated in a canonical stop codon, TAA or TAG, five contain incomplete stop codons, T or TA. Cytochrome b terminates in the mitochondria specific stop codon AGA. This mitogenome provides a valuable resource for future studies of M. myotis and other bat and mammal species.